Prospective clinical study to evaluate the survival of two-piece zirconia implants: a single-center study. 36-month results - Marie-Elise Jennes; Zhen Mao; Ece Atay; Insa Herklotz; Margarita Bessonova; Jeremias Hey; Florian Beuer (International Journal of Implant Dentistry, 2026)
Abstract Purpose To evaluate the 36-month survival and clinical outcomes of two-piece zirconia implants restored with screw-retained glass-ceramic crowns on PEKK abutments. Methods This prospective single-center clinical study evaluated implant survival as the primary outcome, with secondary outcomes including peri-implant soft tissue parameters, marginal bone level changes, and patient-reported outcome measures. Twenty-four patients received single CERALOG Hexalobe two-piece zirconia implants manufactured by ceramic injection molding (CIM) in healed sites. After 6-month submerged healing, implants were restored with provisional screw-retained crowns on PEKK abutments, followed by definitive lithium disilicate crowns (IPS e.max Press) on PEKK abutments secured with titanium abutment screws (25 Ncm). Clinical and radiographic examinations were performed at implant placement, re-entry, definitive loading, and at 12-, 24-, and 36-month follow-ups. Implant survival was analyzed using Kaplan–Meier estimates. Results Of 23 evaluable implants, nine failed within the first 12 months: six due to failed osseointegration (two at re-entry, three during provisional restoration, one after definitive loading) and three due to implant fracture (one during provisional restoration, two after definitive loading). Kaplan-Meier survival rate was 60.9% (95% CI; 41–81%) at 12 months. No additional failures occurred between 12 and 36 months. Peri-implant soft tissue parameters of surviving implants showed favorable trends (PPD: 2.7 ± 0.7 mm at 12 months, 2.0 ± 0.5 mm at 24 months, 1.9 ± 0.8 mm at 36 months; BOP: 26%, 21%, and 18%, respectively; MGI: 0.38 ± 0.36 at 12 months, 0.40 ± 0.76 at 24 months, 0.21 ± 0.48 at 36 months). At the implant level, peri-implant mucositis was diagnosed in 7 of 13 implants (53.8%) at 36 months; no peri-implantitis was observed throughout the observation period. Mean DIB was 1.9 ± 0.6 mm at definitive loading, 1.6 ± 0.5 mm at 24 months, and 1.5 ± 0.9 mm at 36 months. One abutment screw loosening at 24 months was successfully managed. Patients with surviving implants reported high satisfaction scores (overall satisfaction: 5.0 ± 0.0 at 36 months). Conclusions The 39.1% early failure rate within the first 12 months was followed by stable marginal bone levels through 36 months in implants that achieved successful osseointegration. However, peri-implant mucositis remained prevalent at 36 months, underlining the need for peri-implant maintenance. The early post-loading period represents the critical determinant of long-term implant survival in this system. Extended follow-up through 60 months is ongoing.